ANALISIS PERTUMBUHAN EKONOMI DAN KETIMPANGAN PENDAPATAN ANTAR PROPINSI DI INDONESIA PERIODE 1993-2005 - Yadiansyah Yadiansyah (Department of Development Economics, Universitas Sriwijaya, 2007)
This research is aimed to analyze the economic growth of provinces in Indonesia from 1993 to 2005 and also inequality of income among provinces in Indonesia whether within group provinces or between group provinces inequality and the factors that influenced them by using Indeks Theil analysis method. The finding show that the inequality between provinces group in 1993 to 2005 has shown the decreasing trend with oil and gas or without them, eventhough it generally flutuates. The average of inequality among provinces group has reached 0,4694086 with oil and gas where without oil and gas reached 0,540413. The highest inequality of income within provinces group in period 1993-2005 occured in Sulawesi provinces group with inequality average 0,2823691 with oil and gas and 0,282182 without oil and gas. The lowest inequality of income occured in IBT provinces group with inequality average 0,2092553 with oil and gas, without oil and gas 0,07172 occured in Kalimantan group. Keywords : Economical Growth,Â Inequality of Income.